2011
DOI: 10.1016/s1995-7645(11)60166-1
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of Ocimum sanctum Linn. (Lamiaceae) on clinically isolated dermatophytic fungi

Abstract: Ocimum sanctum has antifungal activity, and the leaf extracts may be a useful source for dermatophytic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 11 publications
0
35
0
3
Order By: Relevance
“…The analyzed compounds via GC/MS and HPLC fingerprinting showed constituents in the plants at its crude level and these might be responsible for the inhibition of test isolates. It was mentioned that the complex nature of the phytochemical constituents might be responsible for varying level of activity on fungi isolates and grueling that is required in the determination of process for the target components that is responsible for the fungicidal activity (Balakumar et al, 2011;Ignacimuthu et al, 2011;Stevic et al, 2014;Oro et al, 2015). The fungicidal activity of the extracts might be because of the synergy or antagonistic activities between various elements in the plant extracts (Silva et al, 2010;Balouiri et al, 2016;Salah-Fatnassi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The analyzed compounds via GC/MS and HPLC fingerprinting showed constituents in the plants at its crude level and these might be responsible for the inhibition of test isolates. It was mentioned that the complex nature of the phytochemical constituents might be responsible for varying level of activity on fungi isolates and grueling that is required in the determination of process for the target components that is responsible for the fungicidal activity (Balakumar et al, 2011;Ignacimuthu et al, 2011;Stevic et al, 2014;Oro et al, 2015). The fungicidal activity of the extracts might be because of the synergy or antagonistic activities between various elements in the plant extracts (Silva et al, 2010;Balouiri et al, 2016;Salah-Fatnassi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The amphipathicity of these compounds can explain their interactions with bio-membranes causing the inhibitory effect [30] . It was suggested that extract components cross the cell membrane, interacting with enzymes and proteins of the membrane, thus producing a flux of protons towards the cell exterior which induces changes in the cells and, ultimately their death [31] . It is evident from the results of the current study that susceptibility of pathogens to plant extracts depends upon solvent used for extraction, extract concentration and the organism tested as has been shown by many studies [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may influence the antifungal activity of honey. For example, DeMera and Angert [32][33][34][35][36][37][38] reported that honeys from different phytogeographic regions vary in their ability to inhibit the growth of yeasts, suggesting that botanical origin plays an important role in influencing the antifungal activity. In addition, there are a great variety of components, including phenolic acids, flavonoids and other biomolecules, in different honeys.…”
Section: Discussionmentioning
confidence: 99%